A brewing understanding of the regulation of Bax function by Bcl-xL and Bcl-2. (January 2017) - Renault, Thibaud T.; Dejean, Laurent M.; Manon, Stéphen
Highlights: Bcl-2 homologs expression in yeast is an invaluable tool to decipher molecular aspects of their functions Studies in yeast have revealed unexpected effects of Bcl-xL on Bax localization and activation. Abstract: Bcl-2 family members form a network of protein–protein interactions that regulate apoptosis through permeabilization of the mitochondrial outer membrane. Deciphering this intricate network requires streamlined experimental models, including the heterologous expression in yeast. This approach had previously enabled researchers to identify domains and residues that underlie the conformational changes driving the translocation, the insertion and the oligomerization of the pro-apoptotic protein Bax at the level of the mitochondrial outer membrane. Recent studies that combine experiments in yeast and in mammalian cells have shown the unexpected effect of the anti-apoptotic protein Bcl-xL on the priming of Bax. As demonstrated with the BH3-mimetic molecule ABT-737, this property of Bcl-xL, and of Bcl-2, is crucial to elaborate about how apoptosis could be reactivated in tumoral cells.